The Role of Influence Tactics in Perceptions of Performance Evaluations’ Fairness - Dulebohn, James H.; Ferris, Gerald R. (Academy of Management Journal, 1999)
The present study examined the impact of employees? use of influence tactics on their evaluations of the fairness of the performance evaluation process. Results indicated that the use of supervisor-focused influence tactics was associated with positive procedural justice evaluations, but the use of job-focused influence tactics was associated with negative evaluations. Also, employees? perceptions of decision control and opportunity for formal voice were found to moderate the relationship between influence tactics and procedural justice.